Peranan Pemerintah Kelurahan Bitung Barat Satu dalam Mewujudkan Good Government - Edwin Jacobis; Frangky Robial; Hendry Rumengan; Christian Tarandung; Diana Wangania; Mei Hastuti; Nolvy Ruata (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
The village is a government unit that often receives negative opinions from the public. These opinions include the lack of quality human resources, frequent practices of corruption, collusion and nepotism such as extortion, government officials who are often absent from their places and so on. This study is to determine the extent of the commitment of the Bitung Barat Satu village government in creating Good Government in its area and also to determine the impact of Good Government in providing excellent services in the Bitung Barat Satu village. The sample in this thesis is the Village Head and Village Apparatus totaling 32 (thirty-two) people. Sampling in this study was carried out using a purposive sampling technique. By using data collection analysis techniques including observation, questionnaires, interviews and also stechniques. The Bitung Barat Satu village government has a strong commitment in efforts to achieve Good Government in its area. This is inseparable from the role of the Village Head as a leader who reprimands his subordinates if they do not serve the community well. Apart from that, the village officials and neighborhood heads also strive to provide excellent service to the community in accordance with the principles of Good Government.